Emergency department utilization among youth in foster care: benefits of a patient-centered medical home - Szoko, Nicholas; Phad, Allison; Fournier, Mary E.; Hoganson, George M.; Jonson-Reid, Melissa (Frontiers in Pediatrics, 2025)
BackgroundFoster youth face unique medical, psychological, and social challenges, which can impact patterns of emergency department (ED) utilization. The patient-centered medical home (PCMH) offers a potential model to reduce overutilization of healthcare resources. Little work has examined relationships between PCMHs and ED utilization among foster youth.ObjectivesWe sought to describe longitudinal trends in ED utilization among foster youth in a PCMH.MethodsThis retrospective cohort study leveraged electronic health record data from foster youth seen in a PCMH from 2018 to 2024. Frequency of ED utilization was calculated before, during, and after involvement in the PCMH. We used Poisson generalized linear mixed models to examine associations between each time period (before, during, or after) and the frequency of ED visits, adjusting for age, sex, and race/ethnicity. Results are presented as incidence rate ratios (IRR) with 95% confidence intervals (95% CI).ResultsOut of 857 youth, 525 (61.3%) were female. Median age was 15.5 years (IQR: 14.2–16.8). Most youth were Black or African American (n = 643; 75.0%). The median number of ED visits was three (IQR: 2–7) for the total observation period. Compared to before the PCMH, ED utilization was significantly lower during engagement with the PCMH [IRR: 0.62 (95% CI: 0.54–0.70)]. ED utilization increased after the last PCMH encounter [IRR: 1.12 (95% CI: 1.01–1.24)].ConclusionsEngagement in a PCMH was associated with lower ED utilization among foster youth. Findings suggest that PCMHs may decrease healthcare costs and better support foster youths’ specific health needs.